Emerging technologies for the management of diabetic foot ulceration: a review - Sidhu, Ajaytaj Singh; Harbuzova, Viktoriia (Frontiers in Clinical Diabetes and Healthcare, 2024)
Diabetic foot ulcers (DFUs) and infections are common complications that frequently result in reduced quality of life and even morbidity for patients with diabetes. This paper highlights significant findings in DFU treatments and emerging advanced technologies for monitoring ulceration in patients with diabetes. The management of DFUs requires a multidisciplinary approach that involves patient education. It is well-established that poor glycemic control significantly contributes to diabetic foot ulcer complications, presenting global challenges in quality of life, economics, and resource allocation, affecting approximately half a billion people and potentially leading to lower limb amputation or mortality. Therefore, effective DFU management necessitates a multidisciplinary approach that includes patient education. However, current clinical guidelines for DFU treatment are not performing effectively, resulting in unnecessary increases in financial and emotional burden on patients. Researchers have experimented with advanced technologies and methods, including traditional approaches, to address complications related to DFU healing. This paper also presents the evolution of patents in the field of DFU medication and advanced diagnostic methods, showcasing relevant innovations that may benefit a wide range of researchers.